Mineral trioxide aggregate as a pulpotomy agent in primary molars: An in vivo study - Naik S; Hegde Amitha (Wolters Kluwer Medknow Publications, 2005)
The retention of pulpally involved deciduous tooth in a healthy state until the time of normal exfoliation remains to be one of the challenges for Pedodontists. A scientific noise has been generated about several materials some of which have been popular pulpotomy medicaments. Concerns have been raised about the toxicity and potential carcinogenicity of these materials, and alternatives have been proposed to maintain the partial pulp vitality, however to date no material has been accepted as an ideal pulpotomy agent. Mineral trioxide aggregate (MTA) is a biocompatible material which provides a biological seal. MTA has been proposed as a potential medicament for various pulpal procedures like pulp capping with reversible pulpitis, apexification, repair of root perforations, etc. Hence the present study was done to evaluate the efficacy of MTA as a pulpotomy medicament. A clinical and radiographic evaluation was done on children where MTA was used as pulpotomy medicament in primary molars for a period of 6 months and it was found to be a successful material.